ANALISIS PENGARUH HUTANG LUAR NEGERI (FOREIGN DEBT) DAN PENANAMAN MODAL ASING TERHADAP PDRB TAHUN 2009-2013: STUDI KASUS PADA KOTA MAKASSAR - Ferdiansyah, Kelvin; Mose Saputra Panggabean, Zefanya; Desmawan, Deris (Populer: Jurnal Penelitian Mahasiswa, 2022)
This research will show how external debt and also the level of FDI affect the GRDP of case studies in the Makassar region from 2009-2013. The theory of multiple linear regression analysis is applied in quantitative research methodology. Secondary data from the Makassar Central Bureau of Statistics is used as a data source. Information only regarding the amount of Indonesian loans, the total level of realization of FDI inflows by Indonesia, but also figures regarding the degree and total local national GRDP of Makassar City were all collected using straight literary elements using figures for the period 2009 to 2013 (5 years). The quantitative approach is indeed a technique used to assess the level of guiding decisions in one component having several other characteristics using the SPSS 25 application. Thus, producing an initial model that shows a positive and beneficial effect of the independent variables external debt and FDI is relevant to the dependent variable of City GRDP Macassar. This shows that it is important to increase these two variables because the GRDP level of Makassar city will also increase.